ENVIRONMENTAL IMPACTS OF BENCH BLASTING AT HISARCIK BORON OPEN PIT MINE IN TURKEY - Kahriman A.; Ozer U.; Aksoy M.; Karadogan A.; Tuncer G. (My University, 2006)
This paper presents the results of ground vibration measurements carried out in Hisarcik Boron open pit mine located on the west side of central Anatolia near Kütahya province in Turkey. Within the scope of this study to predict peak particle velocity (PPV) level for this site, ground vibration components were measured for 304 shots during bench blasting. In blasting operations, ANFO (blasting agent), gelatin dynamite (priming), and delay electric detonators (firing) were used as explosives. Parameters of scaled distance (charge quantity per delay and the distance between the source and the station) were recorded carefully and the ground vibration components were measured for all blast events using two different types of vibration monitors (one White Mini-Seis and one Instantel Minimate Plus Model). The absolute distances between shot points and monitor stations were determined using GPS. The equation of square root scaled distance extensively used in the literature was taken into consideration for the prediction of PPV. Then, the data pairs of scaled distance and particle velocity obtained from the 565 event records were analyzed statistically. At the end of statistical evaluation of the data pairs, an empirical relation which gives 50% prediction line with a reasonable correlation coefficient was established between PPV and scaled distance.
Keywords: BLASTING; ENVIRONMENTAL IMPACT; GROUND VIBRATION; AIR BLAST